Effectiveness of training program on attitude and practice of infection control measures among nurses in two teaching hospitals in Ogun State, Nigeria - Adekunbi Abosede Farotimi; Ezekiel Olasunkanmi Ajao; Iyabo Yewande Ademuyiwa; Chinomso Ugochukwu Nwozichi (Wolters Kluwer Medknow Publications, 2018)
Background: Infection control has become a major concern in the health-care system and health-care workers, particularly nurses are at high risk of infection. This study, therefore, examined the effect of a training program on attitude and practice of infection control among nurses in two tertiary hospitals in Ogun State, Nigeria. Materials and Methods: This study adopted a pretest-posttest quasi-experimental design. The sample consisted of 87 participants. The experimental group consisted of 42 registered nurses from Babcock University Teaching Hospital, Ogun state, Nigeria, while the control group consisted of 45 registered nurses from Olabisi Onabanjo University Teaching Hospital, Sagamu, Nigeria. The instrument for data collection was attitude toward components of infection control questionnaire (r = 72) and practice of infection control questionnaire (r = 76). Data were analyzed using SPSS version 21.0 (SPSS Inc. Chicago IL, USA). Results: Findings showed that the mean age in the experimental group was 34.92 ± 8.9 while the control group was 47.43 ± 6.6. The average years of experience for the experimental group were 10.42 ± 9.9 while that of the control group were 21.89 ± 8.7. Responses on attitude showed that 30 participants (69%) had positive attitude in the experimental group compared to 21 participants (46.7%) in the control group. The mean difference was 4.02. Significant difference was observed between mean attitude score of participants in the experimental group and control group (P = 0.03), between mean practice score (P = 0.001), and between self-reported and observed practices (P = 0.000). Conclusion: The training was effective in improving attitude and practice of infection control. Adequate provision of structured training programs on infection control measures is recommended.